Wnt signaling inhibition confers induced synthetic lethality to PARP inhibitors. Issue 4 (30th March 2021) - Angers, Stephane
Abstract : Despite considerable efforts, therapeutic strategies targeting the Wnt pathway are still not clinically available. The pervasive role of Wnt‐βcatenin signaling for the control of stem cells during normal tissue homeostasis makes the on‐target toxicity of available therapeutic grade molecules an important limitation preventing their clinical introduction. The article in this issue of EMBO Molecular Medicine by Kaur et al (2021) reveals that treatment of Wnt‐addicted cancer cells with inhibitors of Wnt signaling induces a state of BRCAness leading to hypersensitivity to PARP inhibitors. This is a new example of induced synthetic lethality that could pave the way for new indications for PARP inhibitors or may contribute to the long‐awaited clinical introduction of therapeutic agents targeting the Wnt pathway. Abstract : S. Angers discusses a new example of induced‐synthetic lethality reported by Kaur et al (this issue of EMBO Mol Med ) that shows that treatment of Wnt‐addicted cancer cells with inhibitors of Wnt signaling induces a state of BRCAness leading to hypersensitivity to PARP inhibitors.